Is the "farm effect" hypothesis still current? Atopy and allergic diseases in rural and urban children in Poland. (3rd October 2018) - Mazur, Agnieszka; Szylling, Anna; Bielecka, Teresa; Strzelak, Agnieszka; Kulus, Marek
ABSTRACT: Objective: The prevalence of allergic diseases has reached epidemic proportions in the Western world. Although farm-living has been associated with a lower prevalence of asthma and atopy, a marked increase in atopy among rural populations after accession to the European Union has been recently reported in Poland. Here, we aimed to investigate the effect of living environment on the prevalence of atopy and allergic diseases in Polish children. Methods: 400 schoolchildren aged 10–14 years from the capital city (223) and from traditional rural part of the country (177) were recruited from June to November 2011. Data on allergic diseases and symptoms were collected by means of questionnaire and physical examination. Atopy was assessed based on skin prick tests (SPTs) reactivity to inhalant allergens in 350 children. Results: A high discrepancy between the prevalence of allergic symptoms (46.7%) and doctor-diagnosed allergic diseases (25%) was demonstrated ( p < 0.0001). Urban children had a higher overall prevalence of allergic diseases and atopy than children living in rural areas, 29.3% versus 17.1% ( p = 0.007) and 33.5% versus 20% ( p = 0.0045), respectively. However, no significant differences in the rates of particular allergic diseases were noted ( p > 0.05). There was higher SPT positivity to trees, grass, corn, weeds, animal dander, and molds in urban children ( p < 0.05). Conclusions: Our data support the protective effect of farm-living on the prevalence of atopy and overall allergic diseases, albeit not on particular allergic diseases, in children in Poland. The underlying mechanisms are not identified, but current socioeconomic changes may be responsible.